Pengaruh Job Insecurity dan Job Stress terhadap Turnover Intention - Ahmad Zidan Al Ghiffari; Rini Safitri (REVITALISASI : Jurnal Ilmu Manajemen, 2022)
This study aims to determine the effect of job insecurity and job stress on turnover intention at the Alfi Putra Cigarette Company. This research is included in the quantitative research. The location of this research is the Alfi Putra Cigarette Company which is located in RT.12, RW.04, Kayujaran Hamlet, Gumbleb Village, Pogalan District, Trenggalek Regency, East Java. The number of samples in this study using 100 respondents. The sample in this study were PR employees. Alfi Putra. The variables in this study consisted of independent variables, namely job insecurity and job stress, while the dependent variable in this study was turnover intention. In this study, there are three hypotheses that were processed using the SmartPLS Version 3. Analysis tool. Based on the research results obtained, it can be concluded that (1) Job Insecurity has a significant positive effect on Turnover Intention, (2) Job Stress has a significant positive effect on Turnover Intention, (3 ) Job Insecurity and Job Stress have a significant positive effect on Turnover Intention.